The Influence of Family Financial Education and Fintech Usage on Financial Management with Financial Self-Efficacy as a Mediating Variable Among Students - Puji Dwi Lestari; Han Tantri Hardini (International Journal of Management Science and Information Technology, 2026)
Technological developments in digital financial services have simplified the way students carry out transactions and access various financial platforms. Nevertheless, this convenience does not automatically lead to build of stronger financial management abilities among students. This study examines the involvement of family financial education and fintech usage on students’ financial management, with financial self-efficacy as a mediating variable. A quantitative design was employed with 177 students from study programs of Accounting and Accounting Education at the Faculty of Economics and Business, State University of Surabaya as respondents. The data collection process utilized a Likert-scale questionnaire, followed by analysis with SEM-PLS 4.0 to assess relationships among variables. The results show that both financial self-efficacies along with students’ financial management are significant positive influenced by family financial education. Fintech usage also positively influences financial management, although it does not significantly influence financial self-efficacy. Furthermore, a significance for enhancing students' financial management is attributed to financial self-efficacy, it also acts as a mediator in the relationship between family financial education and financial management. However, its does not mediate the relationship between fintech usage and financial management.